INTEGRASI SISTEM INFORMASI PADA TINGKATAN SYSTEM SPECIFICATION INTEGRATION PADA KOPERASI KARYAWAN COCA-COLA SIER - Muhammad Harist Murdani (Universitas Trunojoyo Madura, 2019)
Employee Cooperative Coca Cola SIER provides several service for its members. One of it is convenience in buying staple which can be paid using cash or credit, another one is the ease of applying for a loan with lower interest. The cooperative officers also need to write income statement and balance sheet report for all of its activities. Especially reports on salary cuts, store transaction paid by credits and loan payment by its member. All of this process is done individually thus the cooperative management wants to integrate all of them into several information systems with interconnected database. Our purpose in this research is to find the interconnected point, shared member’s data and automatic entry of daily journal of store transaction paid in credits, and implement it into the information system.